VLC signal reconstruction with wavel transform in turbulence environment - Logarasu, R; R. Dhanasekaran, Dr (International Journal of Engineering and Technology, 2018)
Communication involves exchange of data between sender and receiver. The data exchange complexity reduce with wireless data transmission. Conventionally radio signals use for wireless data transmission. The radio frequency limited band width and requirement of new hardware installation make LIFI an optimal solution for wireless data transmission. Since the existing LEDs can be used for data transmission. Recent trends in LiFi have made it possible to transmit data at THz frequency. However, the LiFi signals easily degrade due to surrounding environment noise. In this paper, we propose to reconstruct and eliminate noise in LiFi signal. Wave coefficient block apply for noise level estimation and filter banks use to reconstruct original message signal.Â Â